1980
DOI: 10.1002/ijc.2910260512
|View full text |Cite
|
Sign up to set email alerts
|

Clonal origin and trisomy of chromosome 15 in murine B‐cell malignancies

Abstract: During the course of a multifaceted study of clonality in murine neoplasms we observed two B-lymphoid malignancies. Results of studies with the X-chromosome-linked enzyme phosphoglycerate kinase strongly suggest that these tumors had a clonal origin. Each of them had trisomy 15. This chromosomal abnormality has been found consistently in many murine thymic neoplasms, and has been thought to be specific to tumors of thymic origin. However, the occurrence of trisomy 15 in each of the only two B-cell malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This has been described in spontaneous T-cell lymphomas of the AKR mouse (Dofuku et al, 1975; Herbst et al, 1981), and in a variety of T-cell leukemias induced by RadLV (Wiener et al, 1978a) or dimethylbenzanthracene (Wiener et al, 1978b;Chan et al, 1979;Spira et al, 1980). Other examples in which trisomy 15 has been observed are B-cell lymphomas (Fialkow et al, 1980;Wiener et al, 1981). Rearrangements between chromosome 15,6 and 12 have been described in plasmocytomas (Shepard et al, 1978;Yoshida et al, 1978; al., 1979).…”
Section: Discussionmentioning
confidence: 99%
“…This has been described in spontaneous T-cell lymphomas of the AKR mouse (Dofuku et al, 1975; Herbst et al, 1981), and in a variety of T-cell leukemias induced by RadLV (Wiener et al, 1978a) or dimethylbenzanthracene (Wiener et al, 1978b;Chan et al, 1979;Spira et al, 1980). Other examples in which trisomy 15 has been observed are B-cell lymphomas (Fialkow et al, 1980;Wiener et al, 1981). Rearrangements between chromosome 15,6 and 12 have been described in plasmocytomas (Shepard et al, 1978;Yoshida et al, 1978; al., 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Since then it has been found in other spontaneously derived and carcinogen-, virusor irradation-induced T lymphomas (Wiener et al, 1978~1, 1978c(Wiener et al, 1978~1, , 1981Spira et al, 1980Spira et al, , 1981Haran Ghera, 1978;Chang et al, 1977) as well as in cell lines derived from such lymphomas (Berenson et al, 1981;Bregula et al, 1979;Dowjat and Wlodarska 1981). Some B-cell lymphomas Fialkow et al, 1980), mouse sarcoma and adenocarcinoma lines (Pravtcheva et al, 1981;Manolov, 1979) and epithelial cell lines derived from mouse bladder (Cowell, 1980(Cowell, , 1981 have been also shown to contain trisomy 15. That the duplication of chromosome 15 plays an essential role in T-cell leukemogenesis was shown by recent somatic cell hybridization experiments in which high tumorigenic segregants showed amplification of the tumor-derived chromosome No.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] X-inactivation-based analysis of women with myeloproliferative disease (MPD) and karyotypic analysis have demonstrated that these MPDs are clonal stem cell disorders characterized by acquired somatic mutation in hematopoietic progenitors. [7][8][9][10][11][12] Clinical features of PV include polycythemia in the absence of any cause of secondary erythrocytosis and splenomegaly caused by extramedullary hematopoiesis. Most patients with PV also have varying degrees of leukocytosis and thrombocytosis and variable bone marrow fibrosis that may progress with time.…”
Section: Introductionmentioning
confidence: 99%